A caiçara e o pescador: conhecimento etnobotânico local, legislação e ocupação da orla marítima no município de Lucena, Paraíba, Brasil - Córdula, Eduardo Beltrão de Lucena (2018)
The present research sought to analyze the traditional artisanal construction of the caiçara in the municipality of Lucena, Paraíba, through the botanical knowledge of artisanal fishermen who build them, making use of the botanical tree resource extracted from the Atlantic Forest and Mangrove, with its legal implications of using these, as well as the occupation of the seafront. Since it was a Qualiquantitative research, the Field Survey, Ethnography, Bibliographic and Documentary Research were used as methodology, using Rapport techniques, Non-Participatory Observation, Free and Formal Interview, having as instrument the Semistructured Form, photographic record, georeferencing by GPS and use of digital maps (MapBiomas), registration, numbering, structural measurement (height, width, length and distance of the line between tides) and measurement of the perimeter of the woods used in the caiçaras, Guided Tour, collections for botanical identification of the species indicated in the Free List, and Analysis of data obtained by Methods MPETH, Qualitative Ethnographic Descriptive, Risk Incidence, Use Value and Descriptive Statistics. All activities were authorized by the Fisher Colonies Z-5 and Z-19 Through Letters of Consent and the interviewees signed the Term of Free and Informed Consent, allowing the dissemination of the data obtained, based on the Ethical Conduct for Research on Human Beings, of the National Health Council (Resolution No. 510/2016). This study obtained authorization for its accomplishment, issued by the Ethics Committee of the UFPB, under Protocol n. 0227/2016 and Registration in SISGEN under Cadastre n. A59DF10. With the results obtained, it can be inferred that the caiçara is a very important element within the local culture, which serves as a place of deposition and storage of fishing gear used by fishermen. In the municipality there are 100 caiçaras and the local knowledge involved in this traditional and artisanal culture are running the risk of losing themselves over time, due to the absence in part of this population, in the continuity of vertical and horizontal transmission of the ethnobotanical knowledge involved in its construction and in the resource the local forest used. These resources need adequate management, and should involve municipal, state and federal public agencies, since there is a preferential arrangement of botanical species for their durability and occurrence, so that they remain available over time and thus can be continuously used by the local fishing community. Nine Atlantic Forest and two Mangrove species were identified. In addition to these factors, environmental justice must be present, through the knowledge of current legislation and, although unknown to the local population of Professional Fishermen, allows the occupation of the border to maintain their fishing activity, as well as, the use management of native forest resources. It is concluded that ethnobtanic knowledge and popular culture in this local community of artisanal fishermen need to be preserved, requiring phytosociological studies of the diversity of the species used and their availability, in order to develop the identity and local culture of these fishermen, with a focus in the maintenance of the cultural patrimony that is the caiçara of Lucena, Paraíba.